THE ENGLISH TEACHER TECHNIQUES IN TEACHING READING COMPREHENSION AT SMKN 1 MAMASA - Catherine Wirana S.; Ahmad Munawir; Andi Mega Januarti Putri (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2022)
This study aims to find out (1) the techniques applied by the English teachers in teaching reading comprehension, (2) whether or not the teaching technique is effectively applied in reading comprehension. This study applied a qualitative method. The participants in this research were 4 English teachers and students consisting of 4 classes for observation, and 10 students per class for interview in SMKN 1 Mamasa. Which was taken through purposive sampling technique. The data of this study were collected by observation, interview, and documentation. The obtained data were analyzed in four major phases namely data collection, data reduction, presentation of data and conclusion drawing. The result of this study revealed that, (1) there are four techniques that are applied by English teachers in teaching comprehension, namely read aloud technique (read aloud together / reading aloud one by one), read over and over, questions answering, and enrich vocabulary through translation and memorizing, (2) when teachers taught using those techniques students become enthusiastic about learning, active, participating, able to understand the contents of the reading, and able to answer the questions given by the teacher. The result also shows that the four teachers applied all the techniques effectively in teaching reading comprehension and based on students’ response all of the techniques applied were more than 80% effective. Therefore, the result of this study indicated that the techniques used by the teachers in SMKN 1 Mamasa, such as Read aloud together/reading aloud one by one, read over and over, questions and answering and Enrich vocabulary throung transalation and memorizing, are effective to the students in learning reading comprehensive of English language.